The Influence of Brand Experience, Brand Satisfaction, and Perceived Quality on Brand Loyalty Toward Bottled Drinking Water Products (AMDK) - Nabila Putri Sayekti; Anton Agus Setyawan (Universitas KH. Abdul Chalim Mojokerto, 2025)
In recent years, branding theory has increasingly focused on understanding the relationship between consumers and brands. A brand serves as a symbolic and functional bridge between buyers and sellers, facilitating trust, communication, and emotional connections (Şahin et al., 2011). It plays a key role in influencing consumer purchasing decisions. A brand represents an offering from the seller to the consumer that consistently conveys its character, utility, and assurance of quality (Suntoro & Silintowe, 2020). In this context,